Human Papillomavirus–Associated Oropharyngeal Cancer: Patterns of Nodal Disease. (March 2019) - Plonowska, Karolina A.; Strohl, Madeleine P.; Wang, Steven J.; Ha, Patrick K.; George, Jonathan R.; Heaton, Chase M.; El-Sayed, Ivan H.; Mallen-St. Clair, Jon; Ryan, William R.
Objective: To characterize patterns of neck lymph node (LN) metastases in human papillomavirus (HPV)–associated oropharyngeal squamous cell carcinoma, represented by p16 positivity (p16+OPSCC). Study Design: Case series with chart review. Setting: Tertiary care center. Subjects and Methods: Neck dissection (ND) specimens of nonirradiated p16+OPSCC patients were analyzed for frequencies of clinically evident and occult LNs by neck level. Local, regional, and distant recurrences were reviewed. Results: Seventy p16+OPSCC patients underwent primary site transoral robotic surgery and 82 NDs of varying levels. Metastatic pathologic LNs were found at the following frequencies: 0% (0/28) in level I, 75.6% (62/82) in level II with 57.4% (35/61) in level IIA and 13.1% (8/61) in level IIB, 22.0% (18/82) in level III, 7.0% (5/71) in level IV, and 6.3% (1/16) in level V. The level V LN was clinically evident preoperatively. Five of 21 (23.8%) elective NDs contained occult LNs, all of which were in level II and without extranodal extension. Twenty-seven (38.6%) patients underwent adjuvant radiation; 19 (27.1%) patients underwent adjuvant chemoradiation. With a mean follow-up of 29 months, 3 patients had developed recurrences, with all but 1 patient still alive. All patients who recurred had refused at least a component of indicated adjuvant treatment. Conclusions: For p16+OPSCC, therapeutic NDs should encompass any levels bearing suspicious LNs and levels IIA-B, III, and IV, while elective NDs should be performed and encompass at least levels IIA-B and III. These selective ND plans, followed by indicated adjuvant treatment, are associated with a low nodal recurrence rate.